Maternal health training priorities for nursing and allied professions in Haiti - Amelia J. Brandt; Julio Pedroza; Silvia H. de Bortoli Cassiani; Samantha Brown; Fernando A. Menezes da Silva (Pan American Health Organization, 2020)
Objectives. This study summarizes the findings of a training needs and priority assessment completed in Haiti. Its objective is to describe the characteristics of nursing and allied professions providing first level maternal health care and identify training needs and priorities to inform planning of Human Resources for Health interventions. Methods. A cross-sectional survey was completed between October 2016 and March 2017 by the Pan American Health Organization/World Health Organization Haiti office in collaboration with national health authorities. Participants reached consensus to submit one finalized version of the survey. Data were collected on composition, capacities, and training needs and priorities of traditional birth attendants, community health workers, registered nurses, professional midwives, and auxiliary nurses. Results. Haiti relies heavily on community level workers including community health workers, auxiliary nurses, and traditional birth attendants. Traditional birth attendants attend the majority of Haiti's births, despite having low education levels and not being regulated by the Ministry of Public Health and Population. All professional categories prioritize preventive capacities such as timely identification of complications, while none are trained to manage postpartum hemorrhage, preeclampsia, or eclampsia. Management of obstetric emergencies is a training priority for Haiti but is not part of the scope of work of the nursing and allied health professions included in this study. Conclusions. Community level health workers are key in providing preventive care and referral of complicated pregnancies, but lack of access to providers qualified to treat obstetric complications remains a challenge to reducing maternal mortality.